2015
DOI: 10.1021/jp510027u
|View full text |Cite
|
Sign up to set email alerts
|

SILAR-Deposited Hematite Films for Photoelectrochemical Water Splitting: Effects of Sn, Ti, Thickness, and Nanostructuring

Abstract: Hematite (α-Fe 2 O 3 ) has been widely investigated for photoelectrochemical (PEC) water splitting, but questions remain regarding the nature of improvements induced by different dopants. We report on facile annealing treatments to dope hematite with Ti and Sn, and we provide insight into the effects of the dopant concentration profiles on two key steps of PEC water oxidation: charge separation and interfacial hole transfer. Hematite thin films were deposited by successive ionic layer adsorption and reaction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…As an example, Hisatomi et al reported a 2 nm Nb 2 O 5 buffer layer between hematite and the FTO substrate to reduce recombination at the interface of the semiconductor and the substrate [40]. Abel et al [41] successfully investigated thin films (10-20 nm) of TiO 2 on FTO. They investigated hematite thin films made by a successive ionic layer adsorption and reaction (SILAR) method, with and without TiO 2 underlayer on the FTO.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, Hisatomi et al reported a 2 nm Nb 2 O 5 buffer layer between hematite and the FTO substrate to reduce recombination at the interface of the semiconductor and the substrate [40]. Abel et al [41] successfully investigated thin films (10-20 nm) of TiO 2 on FTO. They investigated hematite thin films made by a successive ionic layer adsorption and reaction (SILAR) method, with and without TiO 2 underlayer on the FTO.…”
Section: Introductionmentioning
confidence: 99%
“…In this method, 0.05 M FeCl 3 and 0.1 M NaOH, were used as iron and hydroxide precursors. 42 The synthesis process is shown in Fig. 2, in which each immersion stage lasted 10 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…8, the tangent lines indicates that the Fe 2 O 3 has an indirect band gap of about 2.04 eV and direct band gap of TiO 2 is about 3.35 eV for our sample; which is agreed with other observations. 42,45 Photoelectrochemical characterization Fig. 9 shows the results of PEC measurements for the a-Fe 2 O 3 / TiO 2 samples.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, element doping, such as doping with Ti, Sn, or Si, can improve the electron conductivity of hematite and hence improve the charge transfer of hematite electrodes. [12][13][14] In particular, Sn ions can be readily incorporated into hematite due to their similar ionic radius and Pauling electronegativity to Fe ions. 15 It was found that Sn-doping is effective to improve the electronic conductivity of hematite.…”
Section: Introductionmentioning
confidence: 99%